Gut Microbiota and Relevant Metabolites Analysis in Alcohol Dependent Mice - Wang, Guanhao; Liu, Qing; Guo, Liang; Zeng, Haijuan; Ding, Chengchao; Zhang, Wentong; Xu, Dongpo; Wang, Xiang; Qiu, Jingxuan; Dong, Qingli; Fan, Ziquan; Zhang, Qi; et al. (Frontiers in Microbiology, 2018)
Alcohol abuse is a major public health crisis. Relative evidences supported that the gut microbiota (GM) played an important role in central nervous system (CNS) function, and the composition of them had changed after alcohol drinking. We sought to explore the function of GM in alcohol dependence. In our study, the GM of mice with alcohol administration was detected through analyzed 16S rRNA gene sequencing and the fecal metabolites were analyzed by LC-MS. The microbial diversity was significantly higher in the alcohol administration group, the abundance of phylum Firmicutes and its class Clostridiales were elevated, meanwhile the abundance of Lachnospiraceae, Alistipes and Odoribacter were changed in the alcohol administration group. Based on LC-MS results, bile acid, secondary bile acid, serotonin and taurine level had varying degrees of changes in alcohol model. From paraffin sections, significantly tissue damage was observed in liver and colon. These findings provide direct evidence that alcohol intake affects the composition of GM, enable a better understanding of the function of GM in the microbiota-gut-brain (MGB) axis, and give a new thought for alcohol addiction treatment.